2016
DOI: 10.1353/hpu.2016.0096
|View full text |Cite|
|
Sign up to set email alerts
|

Patient Experience Of Provider Refusal Of Medicaid Coverage And Its Implications

Abstract: Previous studies show that many physicians do not accept new patients with Medicaid coverage, but no study has examined Medicaid enrollees' actual experience of provider refusal of their coverage and its implications. Using the 2012 National Health Interview Survey, we estimate provider refusal of health insurance coverage reported by 23,992 adults with continuous coverage for the past 12 months. We find that among Medicaid enrollees, 6.73% reported their coverage being refused by a provider in 2012, a rate hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Although we did not collect neighborhood contextual factors, we can speculate about factors explaining differences in outcomes based on insurance coverage, such as lower access to continuous care, because lower public insurance reimbursement to providers may contribute to outpatient clinics limiting or refusing publicly insured patients, thus hampering a child' s ability to receive early and comprehensive care and increasing the risk of having poor asthma control and exacerbations. 41,42 Public insurance recipients are also often financially challenged and have limited education, both of which contribute to low adherence to treatment, and are more likely to live in environments with increased exposure to asthma triggers, making asthma exacerbations more common. 43 Overall, poor outcomes among patients with public insurance may highlight the unmet health care needs of recipients, including limited access to outpatient services and asthma medications.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not collect neighborhood contextual factors, we can speculate about factors explaining differences in outcomes based on insurance coverage, such as lower access to continuous care, because lower public insurance reimbursement to providers may contribute to outpatient clinics limiting or refusing publicly insured patients, thus hampering a child' s ability to receive early and comprehensive care and increasing the risk of having poor asthma control and exacerbations. 41,42 Public insurance recipients are also often financially challenged and have limited education, both of which contribute to low adherence to treatment, and are more likely to live in environments with increased exposure to asthma triggers, making asthma exacerbations more common. 43 Overall, poor outcomes among patients with public insurance may highlight the unmet health care needs of recipients, including limited access to outpatient services and asthma medications.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative studies have indicated that the most cited reason for physicians to not participate in Medicaid was inadequate reimbursement 4 , with frustration among the orthopaedic community in caring for a "challenging, high-risk, and under-insured population while also assuming additional liability without adequate compensation." 5 The shortage of orthopaedic surgeons participating in Medicaid may have dire implications on community health 6,7 and may increase socioeconomic disparities in delivery of orthopaedic care [8][9][10] . Thus, increases in provider reimbursement are often discussed as a potential policy lever to increase access to care for patients with Medicaid [11][12][13] .…”
mentioning
confidence: 99%
“…Additionally, barriers to obtaining health insurance despite national policy change and barriers to obtaining care despite obtaining public health insurance require attention. These barriers emerge from both the patient perspective such as lack of education and awareness as well as from a socioeconomic and system level, such as the inability to take time off work or the refusal by providers to accept new Medicaid‐insured patients 32,33 . An optimistic example can be seen in safety‐net settings where vulnerable patients represent a higher proportion of patients.…”
Section: Discussionmentioning
confidence: 99%